In vitro inhibition of SKOV-3 cell migration as a distinctive feature of progesterone receptor membrane component type 2 versus type 1 - Albrecht, Christian; Huck, Volker; Wehling, Martin; Wendler, Alexandra (Steroids, 2012)
Progesterone receptor membrane component type 2 (PGRMC2) is strongly homologous to PGRMC1 which is highly expressed in ovarian cancer and other cancer cells and was claimed to play an important role in chemotherapy resistance. Whereas PGRMC1 has been extensively characterized in in vitro studies, comparably little is known about PGRMC2. To determine PGRMC2's role in ovarian cancer cell proliferation and mobility PGRMC1- and 2-depleted and -overexpressing SKOV-3 cells were generated. In electric cell-substrate impedance sensing studies, PGRMC2 negatively affects SKOV-3 migration rate if overexpressed; oppositely, depletion was associated with an increased migration rate. PGRMC1 had no effect in this assay. These effects were not associated with f-actin regulation or actin cytoskeleton reorganization. Yet, these highly homologous proteins share many properties. Both PGRMC1 and 2 are localized to the endoplasmic reticulum. As PGRMC1 was reported to interact with cytochrome P450 proteins (CYP) binding of two different CYPs to PGRMC2 was tested; a stable interaction of PGRMC2 with CYP3A4 and CYP21A2 was found in human embryonic kidney cells. For both PGRMC types, cell viability assays revealed no significant differences of SKOV-3 survival in overexpressing and depleted cells. PGRMC2 also does not seem to have any influence on the apoptotic effect of cisplatin or the antiapoptotic effect of progesterone which had been reported for PGRMC1. In contrast to PGRMC1, protein levels of PGRMC2 in SKOV-3 cells are reduced by treatment with cisplatin (30-60μM). In conclusion, we show for the first time that PGRMC2 inhibits migration of SKOV-3 ovarian cancer cells in vitro.
Gesehen am 17.04.2018